Hak Asasi Manusia: Perspektif Islam - Mahmudi, Zaenul (UIN Maulana Malik Ibrahim Malang, 2000)
Along with the advancement of human civilization, conversations concerning human rights issues will not subside in time, because the parameters of a civilized nation is if a civilization has been able to put people in proportion, can